Critical Review of Private Limited Liability Hospitals in the Perspective of Article 34 Paragraph (3) of the 1945 Constitution - Hasrul Buamona; Vicki Dwi Purnomo (Formosa Journal of Social Sciences (FJSS), 2023)
Fulfillment of health one of which is the provision of hospitals which is the responsibility of the government, which cannot be transferred to the private sector like a Limited Liability Company. This has been clearly regulated in Article 34 paragraph (3) of the 1945 Constitution. This then became the background and also became the main focus of the study entitled "Critical Review of Limited Liability Company Private Hospitals in Perspective of Article 34 Paragraph (3) of the 1945 Constitution". This study focuses on the main problem, namely whether private limited liability companies comply with Article 34 paragraph (3) of the 1945 Constitution. The research method used is normative law which is qualitative in nature to analyze data and statutory regulations and Pancasila as the political basis of Indonesian health law, this study used focused interviews with informants. In this study it was concluded that the presence of a private limited liability company hospital is contradictory and not in accordance with Article 34 paragraph (3) of the 1945 Constitution and Pancasila